Empowering older adults' informal, self-directed learning: harnessing the potential of online personal learning networks - Dirk Morrison; Jessica McCutheon (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract Information and communication technologies have had an enormous impact on how we live, work, communicate, re-create, and connect with others. However, there is a paucity of research regarding older adult learners' adoption and adaptation of Internet-based tools, techniques, and resources to support their informal, self-directed lifelong learning goals. This research contributes to our understanding of how and why older adults leverage the Internet and social media tools to create, develop, and maintain online personal learning networks (oPLNs) for the purposes of self-directed knowledge acquisition, personal development, and the facilitation of healthy aging.